EVALUASI PROGRAM LANSIA DI WILAYAH KERJA PUSKESMAS PERAWANG TAHUN 2022 - Neni Suryani; Zulmeliza Rasyid; Kiswanto Kiswanto; Doni Jepisa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Evaluation is a systematic process that aims to collect, analyze, and present useful information that has benchmarks, and the results of these evaluations can be used to make policies. Based on data from the Siak District Health Office in 2020 from 15 Puskesmas in Siak Regency, the lowest data for the elderly in utilizing the Elderly Health Service in the Perawang Health Center with 184 elderly (14.09%). The purpose of the study was to analyze the Elderly Program in the Work Area of the Perawang Health Center. The type of research is qualitative analytic with an observational design. The research location is in the Work Area of the Perawang Health Center, Siak Regency (West Perawang Posyandu). The research time is February to April 2022. There are 6 informants in this research, consisting of 1 key informant (Head of Perawang Health Center), 3 main informants (Elderly Program holder of Perawang Health Center, Midwife, Kader), and 1 supporting informant. (Elderly Program Holder at the Health and Elderly Service). Data were collected utilizing in-depth interviews and observations. Data analysis was collected by triangulation of sources, methods, and data. The results of this study are the planning has been running following the regulations that have been set. Human Resources / Officers are still lacking. Because doctors are lacking, officers have never received training. The facilities are still lacking because there is only 1 kit for the elderly for the public health center and the Posyandu for the elderly does not have a fixed building. Monitoring and evaluation have not gone well because recording and reporting are not synchronized. We hope that Cross Programs will cooperate in implementing the Posyandu for the elderly.Keywords: Evaluation of Elderly Program, Monitoring & Evaluation, Planning, Facilities.